Assessment of Biochemical Abnormalities in Neonatal Seizures: A Study of 60 Patients at a Tertiary Care Hospital - Dighole, Vishwanath (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Neonatal seizures are a significant clinical challenge in newborns, often indicating underlying neurological issues. Identifying biochemical abnormalities can aid in determining the etiology of seizures and guiding treatment. Objective: To assess the prevalence of biochemical abnormalities in neonates presenting with seizures. Material and Methods: This study was conducted in the Department of Pediatrics at a tertiary care hospital. A total of 60 neonates with clinically diagnosed seizures were included. Biochemical investigations included serum electrolytes, glucose levels, and calcium levels. Results: Of the 60 neonates, 30 (50%) exhibited biochemical abnormalities, with hypoglycemia (25%) being the most common. Other abnormalities included hyponatremia (15%), hypocalcemia (10%), and hyperkalemia (5%). Conclusion: Biochemical abnormalities are prevalent in neonates with seizures, particularly hypoglycemia. Prompt biochemical assessment is crucial for appropriate management and improved outcomes. Keywords: Neonatal seizures, Biochemical abnormalities, Hypoglycemia, Hyponatremia.